Legal challenges of combating international cyberterrorism: the NCB Interpol Indonesia and global cooperation - Masyhar, Ali; Utari, Indah Sri; Usman, Usman; Sabri, Ahmad Zaharuddin Sani Ahmad (Faculty of Law, University of Muhammadiyah Malang, 2023)
This paper explores the important role played by the National Central Bureau (NCB) Interpol Indonesia in confronting the complex juridical challenges posed by international cyberterrorism and the relationship between the digital domain and international legal norms, offering insights into how NCB Interpol Indonesia manages this intricate landscape to combat transnational threats. It highlights the critical imperative of establishing a robust legal framework tailored to address the multifaceted dimensions of cyberterrorism, with a steadfast commitment to upholding human rights while maintaining the efficacy of counterterrorism initiatives. The paper examines NCB Interpol Indonesia’s approach to the legal aspects of counterterrorism, shedding light on their role in fostering international cooperation, extradition agreements, and the exchange of critical information. Furthermore, it scrutinizes the challenges associated with reconciling domestic laws and international obligations in the face of rapidly evolving digital tactics employed by terrorist entities. NCB Interpol Indonesia’s experience provides a compelling case study of how a national bureau interfaces with global legal principles, necessitating adaptability, collaboration, and a nuanced understanding of the ever-changing digital terrain. By exploring these juridical challenges, this paper contributes to the broader discourse on counterterrorism in the digital age, with valuable insights into the multifaceted role of NCB Interpol Indonesia and the legal frameworks that underpin their efforts.